The effectiveness of brainstorming teaching method on students' academic engagement, academic vitality and perception learning environment - asgar nakhostin goldoost; Seyyed Mohammad Fatehi Sinesar; Somayye Taklavi (مطالعات روانشناسی تربیتی)
The aim of this study was to determine the effectiveness of brainstorming teaching method on students’ academic engagement, academic vitality, and perception of the learning environment. This study was a quasi-experimental type with a pretest-posttest design with one experimental group and one control group. The statistical population of the study consisted of male students from secondary schools in Germi city in the academic year 2022-2023, with a total of 750 students, of which 30 students were selected using Convenience Sampling and after meeting the inclusion criteria, they were assigned to two groups of 15: experimental and control groups. The tools used in this study were the Academic Vitality Questionnaire by Dehghani Zadeh and Hossein Chari (2012), the Academic Engagement Scale by Reeve (2013), and Perception of the Learning Environment Scale by Sweeney et al. (1994). The brainstorming teaching method program was implemented in 6 sessions of 90 minutes only for the experimental group. The results of multivariate analysis of covariance showed that brainstorming teaching method had a positive effect on improving students’ academic engagement, academic vitality, and perception of the learning environment (P<0.01). Based on the results, it is recommended to use brainstorming teaching method instead of traditional methods in schools.